La entrada de un modelo arquitectónico federiciano en el Reino de Castilla: la Torre de don Fadrique - Molina López, Laura (Anales de Historia del Arte, 2010)
This article will analyze the possible relationships between the architecture promoted by Federico II in the south of Italy and the construction that, later on, was undertaken by the infante Fadrique of Castile in Seville, known as don Fadrique’s Tower. The above mentioned relationships are based on the historical accounts that demonstrate the presence of the infante don Fadrique at the court of Federico II between the years 1240 and 1245.